Raman spectroscopy-based sensitive, fast and reversible vapour phase detection of explosives adsorbed on metal-organic frameworks UiO-67 - Sen Bishwas, Mousumi; Malik, Monika; Poddar, Pankaj (New Journal of Chemistry, 2021)
In this work, we report highly sensitive, selective, rapid, and reversible detection of explosive molecules in the vapour phase, adsorbed on metal-organic frameworks (MOFs) under ambient laboratory conditions. The sensing is based on the quenching of the Raman intensity of a zirconium-based MOF, Zr6O4(OH)(4)(dcppy)(6) (MOF 1, UiO-67-dcppy; dcppy is 2-phenylpyridine-5,4'-dicarboxylate), where 50% of the signal quenches swiftly within similar to 5 s of its exposure to trinitrophenol (TNP) vapours, while 90% of the Raman signal was quenched in 30 s. The high surface area of porous MOFs provides increased adsorption of various nitro analytes. The quenching of Raman peaks resulted from the pi-pi interactions of the analytes with the benzene ring of the MOF. The sensors have also been proven to be reversible and stable by mild heat treatment (80 degrees C for 5 min). These notable results using Raman spectroscopy point to a new and important approach towards explosive sensing using metal-organic frameworks considering their vast versatility. This work emphasizes the importance of a non-invasive and non-destructive technique that can be used to develop handheld vapour phase explosive detectors.